Might be Hydrocavitation Monitored only on Hydraulic Manner and Laws (Global Journals of Research in Engineering, 2023)
Cavitation is a serious problem at hydraulic components especially at pumps hydroenergy turbine runners ship propellers even at blades from windpower generators when performances of those elements machines deplete It means that the cavitation is caused by flowing liquid or gas over the metal surface Severe cavitation always leads to the erosion at the impigement metal surface Many conclusions were stated that for cavitation are responsible the hydraulic demands while material properties commonly not In many hydraulic approaches the starting point is the speed flow of running fluid water oil or gas and also other data about hydraulic circumstances and laws Bernuli equation etc Also in studying the nature of loads which act on turbine runner blade many attempts were made on measuring the noice frequency signals etc but without deeper understanding the characteristics of used material Cavitation here will be considered as a result of contact flowing water metal at turbine runner mainly from aspect of material characteristics not from a hydrodynamic flow demands More attention will be payed on the characteristics of materials preferably used for producing of turbine runners such as crystal grain size or shape the presence of non-metallic inclusions or micro alloying elements
Keywords: hydrocavitation; stainless steel; stabilizing elements; grain size; coatings